Commercial Gold(I) and Gold(III) Compounds Supported on Carbon Materials as Greener Catalysts for the Oxidation of Alkanes and Alcohols. Issue 8 (5th March 2018) - Carabineiro, Sónia A. C.; Martins, Luísa M. D. R. S.; Pombeiro, Armando J. L.; Figueiredo, José L.
Abstract: Strategies are presented for single‐pot efficient oxidative functionalization of cyclohexane and alcohols, under mild conditions, catalysed by Au(I) or Au(III) compounds supported on different carbon materials with three different surface treatments. The obtained materials were tested for the oxidation of cyclohexane under mild conditions (room temperature and atmospheric pressure), using an environmentally friendly oxidant ( tert ‐butyl hydroperoxide, TBHP, 70 % aqueous solution). All materials were very selective to the production of cyclohexanol and cyclohexanone with no trace of by‐products detected. The catalysts were also tested in the selective oxidation of methyl benzyl alcohol, cyclohexanol, and 2‐octanol with TBHP, under microwave irradiation, to the corresponding aldehydes or ketones. In general, better results are obtained for the heterogenised complexes and that the most efficient support is CNT‐ox‐Na. This is the first report on the oxidation of C−H bonds using the mononuclear gold complexes used; only the oxidation of unsaturated units had been reported previously. The sp 3 ‐C−H activation is much more difficult than the oxidation of unsaturated molecules with molecular oxidants. Abstract : Efficient single‐pot oxidative functionalization of cyclohexane and alcohols, under mild conditions, was catalysed by Au I or Au III complexes supported on activated carbon, carbon xerogel, and multi‐walled carbon nanotubes.